High-temperature configurations of dimers in Si (001) surface layers - Kiv, A.E.; Maksymova, T.I.; Moiseenko, N.V.; Soloviev, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Molecular Dynamics (MD) simulation of Si (001) surface layers was performed. In the modified algorithm of MD the potential is corrected on each step of calculation. The corrections account the re-hybridization of chemical bonds in relaxation processes. It was found that the high-temperature relaxation of Si surface layers leads to formation of Quasi-Disordered Phase (QDP). QDP is spread from the first layer up to the forth-fifth layer. In all these layers dimers are formed. Their characteristics (length distribution and space orientation) change from layer to layer. They differ significantly from dimers formed at lower temperatures.